UNDERSTANDING LEGAL BARRIERS TO FOREIGN INVESTMENT IN AFGHANISTAN: A CASE STUDY IN HERAT INDUSTRIAL ZONE - Alizai, Ghulam Shah Adel (International Journal of Research -GRANTHAALAYAH, 2020)
Since a century ago, there have been many efforts to attract foreign investment in Afghanistan. These efforts include the codification of laws and policies and the provision of facilities for participation of foreign companies in the Afghan economy through partnership with the government and partnership with private sector in this country. Since 2001, with the support of the market economy system in Afghanistan’s constitution and the reform of some governmental institutions, these efforts have been accelerating, hoping that encouraging foreign investors and their presence in the market will improve the economic situation. Unfortunately, these efforts have failed to meet the market expectations and the Afghanistan’s government purposes in order to attract foreign investment in Afghanistan. Even in 2014, and after that, the outflow of capital (domestic and foreign) has also been reported from the economy of Afghanistan. Various variables can be considered as an obstacle to the development of foreign investment in Afghanistan, war, corruption, lack of infrastructure, lack of energy, lack of trained workforce and non-accountability of the legal system are in this category. In this research, it was assumed that the existing challenges in different sectors of legal framework of foreign investment in Afghanistan are the main obstacles to the growth of foreign investment in this country. In order to prove the hypothesis, the study was carried out using the experimental research method by referring to the investors and experts in the economic zone of Herat in western Afghanistan. The research results indicate that in some sectors, the legal system needs to be reformed, but in general and by comparing the legal system with other variables, the measure of investors’ satisfaction is satisfactory, and regulations are not as the main obstacle to the growth of foreign investment in Afghanistan, thus based on the analysis of data, the existing challenges in the laws and policies is not the main obstacle to the growth of foreign investment in Afghanistan. Therefore, it is necessary for Afghanistan’s government to take into account the challenges such as security problems, corruption, lack of infrastructure, lack of energy and lack of trained workforce and take steps to address them.